The Implementation of Problem-Based Learning Model and SETS Vision in Sadeng 03 Elementary School to Enhance 4th Grade Studentsâ Activities and Learning Outcomes - Setyasto, Novi; Wijayama, Bayu (Proceedings of the UR International Conference on Educational Sciences, 2018)
Based on preliminary observation in Sadeng 03 Semarang elementary school has been found some challenges which needed to be overcome in the learning process, especially in 4th grade. Teacher has not implemented yet problem-based learning whichis suggested byRegulation of Education and Culture Minister Number 22/ 2016 about Process Standardto be implemented in the learning process. Students tended to be passive learners and their learning outcomes were low. This was classroom action research which was divided into three cycles. This study aimed to enhance studentsâ activities, and learning outcomes by applying problem-based learning model and science, environment, technology, society (SETS) Vision in the learning process. The samples of this research were 30 students of 4th grade. Data was derived from observation, test, field note, and documentation. Qualitative and quantitative description were used in this research.The results showed that implementation ofPBL and SETS vision was effective to improve studentsâ activities proved by the improvements of studentsâ activities from 1st cycle (high category) to the 2nd and 3rd cycle (very high category). In addition, there were found improvements of studentsâ learning outcomes in every cycle which showed by the increases of average scores from 60 (pre-cycle) to 80 (3rd cycle). In conclusion, the implementation of PBL and SETS vision was effective to level up the studentsâactivities, and learning outcomes of 4th grade students of Sadeng 03 elementary school.